The impact of thiamine supplementation on blood pressure, serum lipids and C-reactive protein in individuals with hyperglycemia: A randomised, double-blind cross-over trial - Alaei-Shahmiri, F.; Soares, Mario; Zhao, Y.; Sherriff, Jill (Elsevier Ltd, 2015)
Background: The adverse effects of hyperglycemia may be potentiated when it is accompanied with hypertension and dyslipidemia. This study assessed the effects of high dose thiamine on blood pressure, serum lipids and C-reactive protein (hs-CRP) in individuals with impaired glucose metabolism.: Methods: This was a double-blind, randomised trial, where 12 hyperglycemic subjects (10 cases of impaired glucose tolerance and 2 new cases of type 2 diabetes mellitus) received both placebo and thiamine capsules (3. ×. 100. mg/day) for six weeks in a cross-over manner. Anthropometric measurements, systolic and diastolic blood pressure (SBP & DBP), serum cholesterol, triglyceride, HDL-cholesterol, LDL-cholesterol, hs-CRP and thiamine status were evaluated at the start, after three weeks and on the completion of each arm.: Results: DBP was significantly decreased in participants consuming thiamine supplements for six weeks (67.9. ±. 5.8. mm Hg) relative to baseline (71.4. ±. 7.4. mm Hg, p = 0.005) and week 3 (70.9.±. 5.8. mm Hg, p = 0.02). This was accompanied with a tendency toward a lower SBP at week six relative to baseline (116.5. ±. 11.0 vs. 120.7. ±. 15.3. mm Hg, p = 0.06). Also, mean arterial pressure (MAP) determined in the supplement arm after six weeks was significantly lower than baseline (84.1. ±. 6.5 vs. 87.8. ±. 9.0, p = 0.005). These variables did not change in the placebo arm. No significant change was detected in the supplement or placebo arms when lipid profile and hs-CRP were assessed.: Conclusion/interpretation: High dose thiamine supplementation may have beneficial effects on the blood pressure of individuals with hyperglycemia at early stages, and may have a role in the prevention of further vascular complications. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12611000051943.